Von Willebrand factor increases in experimental cerebral malaria but is not essential for late‐stage pathogenesis in mice. (27th August 2020) - Kraisin, Sirima; Martinod, Kimberly; Desender, Linda; Pareyn, Inge; Verhenne, Sebastien; Deckmyn, Hans; Vanhoorelbeke, Karen; Van den Steen, Philippe E.; De Meyer, Simon F.
Abstract: Background: Cerebral malaria (CM) is the most severe complication of malaria. Endothelial activation, cytokine release, and vascular obstruction are essential hallmarks of CM. Clinical studies have suggested a link between von Willebrand factor (VWF) and malaria pathology. Objectives: To investigate the contribution of VWF in the pathogenesis of experimental cerebral malaria (ECM). Methods: Both Vwf +/+ and Vwf −/− mice were infected with Plasmodium berghei ANKA ( Pb ANKA) to induce ECM. Alterations of plasma VWF and ADAMTS13 (a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13), platelet count, neurological features, and accumulation of platelets and leukocytes in the brain were examined following infection. Results: Plasma VWF levels significantly increased upon Pb ANKA infection in Vwf +/+ animals. While ADAMTS13 activity was not affected, high molecular weight VWF multimers disappeared at the end‐stage ECM, possibly due to an ongoing hypercoagulability. Although the number of reticulocytes, a preferential target for the parasites, was increased in Vwf −/− mice compared to Vwf +/+ mice early after infection, parasitemia levels did not markedly differ between the two groups. Interestingly, Vwf −/− mice manifested overall clinical ECM features similar to those observed in Vwf +/+ animals. At day 8.5 post‐infection, however, clinical ECM features in Vwf −/− mice were slightly more beneficial than in Vwf +/+ animals. Despite these minor differences, overall survival was not different between Vwf −/− and Vwf +/+ mice. Similarly, Pb ANKA‐induced thrombocytopenia, leukocyte, and platelet accumulations in the brain were not altered by the absence of VWF. Conclusions: Our study suggests that increased VWF concentration is a hallmark of ECM. However, VWF does not have a major influence in modulating late‐stage ECM pathogenesis.